The Association of IGFBP7 Gene Polymorphism on Lamb Meat Quality in Javanese Thin-Tailed Sheep - Komarudin; Listyarini, K.; Budiman, C.; Sumantri, C.; Gunawan, A. (Faculty of Animal Science, IPB University, 2024)
The insulin-like growth factor binding-protein 7 (IGFBP7) gene is one of the potential genes related to meat quality. The objective of the current study was to evaluate polymorphism of the IGFBP7 gene (g.72351183A>C) and its association with meat quality traits in the Javanese thin-tailed (JTT) sheep. A comprehensive analysis was conducted on 88 JTT male sheep to examine their fatty acid composition, carcass characteristics, carcass retail cuts, and the physical properties of lamb meat. The polymorphism was detected using the PCR-RFLP technique. The association between the IGFBP7 gene polymorphism and the observed variables of meat quality was evaluated using one-way analysis of variance (ANOVA). The study results indicated that the IGFBP7 gene was polymorphic in JTT sheep population, with the allele distribution conforming to Hardy-Weinberg equilibrium. The AA genotype was found to be predominant. The IGFBP7 gene variants were associated (p<0.05) with erucic acid, linoleic acid, eicosapentaenoic acid, and total polyunsaturated fatty acid (PUFA). Sheep possesing the CC genotype exhibited the highest levels of linoleic acid, eicosapentaenoic acid, and total PUFA in comparison to those with AA and AC genotypes. However, the IGFBP7 gene polymorphism was not associated with carcass characteristics, carcass retail cuts, and physical properties of meat. These findings suggest that the IGFBP7 gene is a promising candidate marker for improving fatty acid composition in JTT sheep.